2018
DOI: 10.1038/s41598-018-32465-4
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection is not related to increased carotid intima-media thickness in general population

Abstract: The aim is to determine whether there is an independent association between Hp infection and carotid intima-media thickness (CIMT) in a cross-section observational study. Among of 14588 routine health check-up participants, 13770 subjects underwent the 13C-urea breath test (13C-UBT) and ultrasound measurement of CIMT. Traditional atherosclerotic risk factors were also recorded. The ratio of increased CIMT in Hp positive group (28.6%) was not significant difference compared with Hp negative group (29.7%) (p = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…Thus, a negative association was observed for female sex, while a positive association was observed for age and SBP. HDL-C appeared also as an independent factor negatively related to IMT-CC, which had been previously observed and related to its antioxidant activitiy 37 . We also observed the use of diuretics as an independent positive contributor though it did not correlated with serum Mg, which does not agree with the findings reported in the Atherosclerosis Risk in Communities Study (ARIC) cohort reporting that higher serum Mg levels associated to lower prevalence of diuretic use 7 .…”
Section: Discussionsupporting
confidence: 75%
“…Thus, a negative association was observed for female sex, while a positive association was observed for age and SBP. HDL-C appeared also as an independent factor negatively related to IMT-CC, which had been previously observed and related to its antioxidant activitiy 37 . We also observed the use of diuretics as an independent positive contributor though it did not correlated with serum Mg, which does not agree with the findings reported in the Atherosclerosis Risk in Communities Study (ARIC) cohort reporting that higher serum Mg levels associated to lower prevalence of diuretic use 7 .…”
Section: Discussionsupporting
confidence: 75%
“…A cross-sectional study of 13,770 general population found that after adjusting for a variety of factors, there is almost no evidence that there is an association between H. pylori and CIMT. 61 In contrast, a small sample size study found that positive H. pylori was associated with an increase in CIMT and believed that H. pylori might play a role in the process of AS. 32 At the same time, Jin Huashan (2018)…”
Section: F I G U R E 3 Meta-analysis Results Of Cimt Related Literatu...mentioning
confidence: 96%
“…What needs attention is that for every 100 mm increase in the absolute value of CIMT, the probability of stroke will increase by 13% to 18%, and the probability of myocardial infarction will increase by 10% to 15% in the future. A cross‐sectional study of 13,770 general population found that after adjusting for a variety of factors, there is almost no evidence that there is an association between H. pylori and CIMT 61 . In contrast, a small sample size study found that positive H. pylori was associated with an increase in CIMT and believed that H. pylori might play a role in the process of AS 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of atherosclerosis is complex. In addition to the identified risk factors, studies have proposed that HP infection may be a risk factor for CAS, but some researchers still hold the opposite opinion ( 5 , 22 , 23 ). We conducted a cross-sectional study of 1,424 subjects in Jidong from 2014 to 2015 to explore the association between HP and CAS.…”
Section: Discussionmentioning
confidence: 99%
“…Although it colonizes the digestive tract, increasing evidence has shown that HP is associated with extragastric diseases such as CVD. However, some researchers have different perspectives on the existence of an association between HP and CAS ( 5 ). This is a controversial topic in epidemiological, pathological, and clinical studies ( 6 ).…”
Section: Introductionmentioning
confidence: 99%